2016
DOI: 10.3390/app7010036
|View full text |Cite
|
Sign up to set email alerts
|

Dual-Fuel Combustion for Future Clean and Efficient Compression Ignition Engines

Abstract: Stringent emissions limits introduced for internal combustion engines impose a major challenge for the research community. The technological solution adopted by the manufactures of diesel engines to meet the NOx and particle matter values imposed in the EURO VI regulation relies on using selective catalytic reduction and particulate filter systems, which increases the complexity and cost of the engine. Alternatively, several new combustion modes aimed at avoiding the formation of these two pollutants by promot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 53 publications
(30 citation statements)
references
References 41 publications
(26 reference statements)
0
30
0
Order By: Relevance
“…12 reveals that HC emissions are higher for D-E85. Previous works have shown that HC emissions levels are well related to the quantity of low reactivity fuel injected in the cylinder [50]. In this sense, it was found that the amount of low reactivity fuel that reaches the crevice regions is not burned because the impossibility of the high temperature gas to arrive to this cold zone, mainly when using re-entrant piston bowl geometries [51].…”
Section: Diesel-e85 Vs Diesel-gasoline Operationmentioning
confidence: 99%
“…12 reveals that HC emissions are higher for D-E85. Previous works have shown that HC emissions levels are well related to the quantity of low reactivity fuel injected in the cylinder [50]. In this sense, it was found that the amount of low reactivity fuel that reaches the crevice regions is not burned because the impossibility of the high temperature gas to arrive to this cold zone, mainly when using re-entrant piston bowl geometries [51].…”
Section: Diesel-e85 Vs Diesel-gasoline Operationmentioning
confidence: 99%
“…A revolution is approaching with respect to traditional gasoline and diesel engines making the boundaries between them disappear as deeper knowledge and greater control of the combustion process is acquired [34]. Advanced injection systems [35,36], turbochargers [37,38], organic Rankine cycles (ORC) [39], hybridization [40,41], multifuel solutions [42][43][44], or advanced combustion concepts are becoming a part of the ICE context. All these strategies are dedicated to extract every Joule of energy from the fuel.…”
Section: What Can the New Generation Of Ice Provide?mentioning
confidence: 99%
“…The Rate of Heat Release (RoHR) was obtained through the pressure signal processing. The details of the RoHR calculation are fully described in [43]. Also, the bulk gas temperature and the maximum pressure gradient for the different tests were obtained from CALMEC.…”
Section: In-cylinder Pressure Signal Processingmentioning
confidence: 99%